Competencies Associated With Australian and New Zealand Podiatrists' Perceptions of Their Preparedness for Graduate Clinical Practice - Katrina Reynolds; Evelyne Rathbone; Michelle McLean (Bond University, 2023)
Podiatry training institutions are responsible for preparing future podiatrists to be competent and safe practitioners. This follow-up study investigated podiatrists' self-reported preparedness to practice through their ratings of various competencies. An online retrospective survey comprising closed and open-ended questions was distributed to registered and practising podiatrists in Australia and New Zealand. Of the 74 podiatrists who completed the survey, 75.7% felt "prepared" for clinical practice at graduation, with preparedness univariately associated with being female (p = .042), overall perception of clinical competence (p = .004), preparedness for clinical placement as a student (p < .001), theoretical knowledge (p < .001), manual skills (p = .002), and clinical competence standards (p < .001). Multivariable analysis identified preparedness for student clinical placement (OR = 8.95, 95%CI 1.92 - 41.76) and overall theoretical knowledge (OR = 19.29, 95%CI 3.76 - 99.13) being significantly associated with perceived preparedness for practice. Age, qualification, and graduation year were not associated with perceived preparedness. Positive clinical placement experiences enhanced their perceived preparedness, while limited clinical exposure hindered preparedness, potentially resulting in a probable theory-practice gap, and lowered professional self-efficacy. While generally feeling prepared to practice as podiatrists at graduation, they identified the need for additional hands-on learning with early patient exposure in diverse settings during their training, which should improve self-efficacy.